2008
DOI: 10.1111/j.1442-200x.2007.02442.x
|View full text |Cite
|
Sign up to set email alerts
|

Level of oxidative stress and damage in erythrocytes in apprentices indirectly exposed to lead

Abstract: Chronic indirect Pb exposure results in lipid peroxidation in erythrocytes of apprentices via OS, and duration of Pb exposure is a reliable marker of Pb toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
(61 reference statements)
5
30
0
4
Order By: Relevance
“…Decreased α-tocopherol concentrations were also reported in a study by Ergurhan-Ilhan et al (42) who examined apprentices exposed to low doses of lead (PbB = 7.9±5.2 μg/dl). Moreover, Caylak et al (44) showed decreased level of vitamin E in rats that were orally exposed to lead acetate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Decreased α-tocopherol concentrations were also reported in a study by Ergurhan-Ilhan et al (42) who examined apprentices exposed to low doses of lead (PbB = 7.9±5.2 μg/dl). Moreover, Caylak et al (44) showed decreased level of vitamin E in rats that were orally exposed to lead acetate.…”
Section: Discussionmentioning
confidence: 78%
“…It was reported that supplementation with the vitamin may increase glutathione production and lower lipid peroxide concentrations (41). This supplementation may also prevent the lead-induced inhibition of superoxide dismutase (SOD) and catalase (42). Furthermore, α-tocopherol weakly increases ALAD levels in rabbits with chronic plumbism (43).…”
Section: Discussionmentioning
confidence: 99%
“…Struzynska et al (2002) investigated the effect of lead on glutathione system and observed in cerebellum an increase in total glutathione content comparable to those in other regions of brain. According to Ergurhan-Ilhan et al (2008), the GPx activity was found to increase in erythrocytes of apprentices chronically exposed to lead. Adonaylo and Oteiza (1999) also made a similar observation of increase in GPx activity in whole brain on exposure to lead and they correlated this increase to the protective response of the brain tissue to oxidative stress caused by lead.…”
Section: Discussionmentioning
confidence: 96%
“…Lead causes toxicity not only to the developing brain Bellinger, 2007) but also to the adults on occupational exposure (Gracia and Snodgrass, 2007;Schwartz and Hu, 2007;Ergurhan-Ilhan et al, 2008). According to Patrick (2006a) and Hu and Woolf (2007), lead contamination results in cognitive dysfunction, neurological damage, neurobehavioural disorders, hypertension, renal failure and reproductive defects in adults.…”
Section: Introductionmentioning
confidence: 97%
“…Table 4 shows that MDA levels were the most frequently used biomarker for measuring LPO. Twenty studies found MDA levels to be signifi cantly higher in leadexposed groups (BLL, 5.4-317.3 μg/dL) than in the control groups (BLL, 0-12.5 μg/ dL) (Tenchova et al 1997 ;Ye et al 1999 ;Yucebilgiç et al 2003 ;Gurer-Orhan et al 2004 ;Kasperczyk et al 2004aKasperczyk et al , b , 2009Kasperczyk et al , 2013aOktem et al 2004 ;Patil et al 2006a , b ;Garçon et al 2007 ;Ergurhan-Ilhan et al 2008 ;Khan et al 2008 ;Mohammad et al 2008 ;Grover et al 2010 ;Permpongpaiboon et al 2011 ;Singh et al 2013 ). Among these, 15 studies reported a signifi cant positive correlation between BLLs and MDA concentrations ( r = 0.15-0.80; p < 0.05).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 96%